Alternative scenarios for BRAC University - Inayatullah, Sohail Tahir; Ahmed, Shakil; Alam, Pushpita; Davis, Susan; Hashemi, Syed (© 2013 Emerald Group Publishing Limited., 2016)
This article was published in the On the Horizon [© Emerald Group Publishing Limited.] and the definite version is available at : http://doi.org/10.1108/OTH-01-2013-0006. The Journal's website is at: http://www.emeraldinsight.com/doi/pdfplus/10.1108/OTH-01-2013-0006